EDUKASI PERAWATAN WAJAH BERJERAWAT AKIBAT PENGGUNAAN MASKER PADA MASA PANDEMI COVID-19 - yuhara, Novena; Rahmavika, Tabita; Imansari, Aulia Nadya Rizki (Universitas Kristen Immanuel, 2023)
Acne (acne vulgaris) is a skin disease caused by chronic inflammation with a complex pathogenesis, involving the sebaceous glands, follicular hyperkeratinization, excessive bacterial colonization, immune reactions, and inflammation. The method of implementing this community service activity is by using the exposure method in the form of mini seminars and mini talk shows, namely providing an explanation of the introduction of acne, the causative factors, and how to prevent it through the use of natural ingredients turmeric to participants, namely young women from various circles online. The purpose of this community service is to provide education about acne facial treatments and the use of natural ingredients that can be used as an alternative to problems with acne prone skin. The positive impact that can be felt on this community service after being educated is that participants, namely teenagers from various circles, have received very useful information and gained knowledge about making acne facial care products from natural ingredients, namely turmeric, with an increase in understanding of the material by 92%.